“Poetry! what is your name?” – proper names in Julian Tuwim’s poems - Graf, Magdalena (Papers in Linguistics, 2024)
The article is concerned with proper names in selected poems by Julian Tuwim. The poet’s achievements are discussed in many studies, especially in literary ones. Researchers (e.g. Michał Głowiński, Ryszard Matuszewski) investigated the most important aspects of his poetry and the features of its poetics. They also paid attention to the linguistic aspect of Tuwim’s writing, but they were not much interested in the onymic layer of his poems. Meanwhile, Tuwim’s poetry is the source of a rich collection of proper names, appearing on their own or constituting elements of metaphors and similes. The article discusses selected names from the perspective of their functionality, considering also the usefulness of research tools of literary onomastics in the interpretation of onomastics in poetic texts